Convective boundary layer flow of viscoelastic micropolar fluid over bluff body with aligned magnetic effect - Laila Amera, Aziz (2024)
Viscoelastic micropolar fluid is a non-Newtonian fluid that exhibits both viscous and elastic properties along with the presence of microstructures. Diverse materials such as blood, synovial fluid, liquid crystals, and certain lubricants exhibit the characteristics of viscoelastic micropolar fluids, rendering this study advantageous for a broad spectrum of industrial, engineering, and biomedical applications. For instance, this study could help to understand fluid behaviour around cylinder extruders in polymer processing. Due to the complex nature of this fluid its governing equations involve fourth-order derivatives in the momentum equations that require an additional boundary condition to obtain a complete solution. This thesis investigates the behaviour of viscoelastic micropolar fluid flow over bluff bodies, specifically horizontal circular cylinders and spheres. Initially, the study focuses on boundary layer flow, and subsequently extends its analysis to encompass free and mixed convection scenarios. Free convection occurs due to density differences in the fluid caused by temperature gradients, often involving fluid behaviour around heated or cooled surfaces, while mixed convection involves both free convection and forced fluid motion, typically from an external source. The governing boundary layer equations are transformed into the non-dimensional form before they are converted into a set of non-similar boundary layer equations. Then, the Keller-box scheme, which is a finite-difference method, was used to solve these equations numerically employing the Fortran programming language. The results are displayed in both tabular and graphical forms include velocity, temperature and microrotation profiles, skin friction and heat transfer for various parameters such as viscoelastic, micropolar, mixed convection, magnetic as well as the aligned angle of the magnetic field for the case of constant wall temperature. From the study, it is found that velocity, temperature and micro-rotation behaviour of viscoelastic micropolar fluid is influenced by its viscoelastic nature as well as the presence of microstructures in the fluid. In general, viscoelasticity and microstructures tend to retard the velocity of the flow but enhance the temperature and microrotation profiles. These characteristics also have a leverage on the heat transfer and skin friction properties of the fluid flow while exerting control on the boundary layer separation on the bluff body. Higher viscoelasticity leads to a reduction in heat transfer and skin friction coefficient, while higher micropolarity results in the opposite behavior. In addition, the aligned angle parameter is also recognized as a limiting factor for the strength of the magnetic field and the strength is maximised when the magnetic field lines and flow velocity vectors are orthogonal. The mixed convection parameter has the same effect on horizontal circular cylinder and sphere. Elevating the mixed convection parameter leads to augmented flow velocity, skin friction coefficient, and heat transfer, while simultaneously impeding microrotation and temperature profiles. Overall, the issue addressed in this thesis is not solely confined to the present geometry and fluid flow impact; rather, it can be extrapolated to encompass alternative geometries and supplementary effects.